The Use Of Quartz Sand Filters To Improve Iron (Fe) Levels In Well Water Quality - Azillia Prameswara, Kirana Noor; Santjoko, Herman; Haryono, Haryono; Narto, Narto (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Water resource useful for humans in daily lives. Water needs to be processed to make water suitable use. Water quality can affect public health and environmental problems, Iron (Fe) levels in water when consumed can cause health problems. The maximum limit Iron (Fe) levels in water is 0,2 mg/L Permenkes No. 2 of 2023. survey conducted Sindumartani well water, Ngemplak, Sleman with an examination result of 3 mg/L. at Organic Iron (Fe) level in PDAM Sleman Unit Nogotirto well water with examination result of 3 mg/L at of the Inorganic Iron (Fe) level. This study uses a quasi-exsperimen with Pre test- Post test with control Group Design to determine the difference in the decrease in Organic Iron (Fe) and Inorganic Iron (Fe) levels after filtration using quartz sand media in well water. The results of this study on water treatment with KMnO4 quartz sand to reduce Inorganic Iron (Fe) levels in water by an average of 2.35 mg/L (88,13%) and Organic Iron (Fe) levels in water by an average of 1.71 mg/L (46,80%). Oxidation process in quartz sand with the highest effective percentage reduction inorganic iron (Fe) levels of 88.13%. Statistical test results show a Sig value of 0.002>0.05 the Independent Sample T-Test, meaning a difference in Organic Iron (Fe) Levels and Inorganic Iron (Fe) Levels before after filtration using quartz sand. Houshing Filter quartz sand media with a volume 700 ml to reduce 88,13% Iron (Fe) Anorgnaik levels well water.